1977
DOI: 10.1139/v77-531
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis, thermochromism, and cycloadditive properties of an O-methylenethioquinone system

Abstract: ). The irradiation of 4,5-benzo-1,2-dithiole-3-thione (1) in the presence of cyclopentene and of tetramethylethylene gives 1 : 1 adducts. In solution these adducts are in equilibrium with eightmembered-ring dimers. The thermodynamic parameters for this equilibrium have been determined. The available evidence suggests a head-to-head configuration. These same monomeric adducts give Diels-Alder addition products with normal dienophiles, but also react similarly with simple thiones (adamantanethione, norbornanethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Nur bei der N,N'-Diphenylverbindung 4p, bei der wir einen Beitrag der Mercaptoform annehmen, liegt die Resonanz von C-2 bei hoherem Feld (6 = 132; s. Experimcnteller Teil). (9,CH@) 3.80 (4, 3.62 w q , w , z ) 4.28 (s, CH2E) Aus Gleichgewicht 4 j ( Z , E , R2, R3…”
Section: C-nmr-spektrenunclassified
“…Nur bei der N,N'-Diphenylverbindung 4p, bei der wir einen Beitrag der Mercaptoform annehmen, liegt die Resonanz von C-2 bei hoherem Feld (6 = 132; s. Experimcnteller Teil). (9,CH@) 3.80 (4, 3.62 w q , w , z ) 4.28 (s, CH2E) Aus Gleichgewicht 4 j ( Z , E , R2, R3…”
Section: C-nmr-spektrenunclassified
“…In this reaction the thione l a parallels the reaction of benzo-1,2-dithiole-3-thione with dimethyl acetylenedicarboxylate (2), but there the monoadduct rapidly reacted with more acetylenic ester to form a diadduct. No such monoadduct dimers are reported from the reaction of the structurally related benzo-or naphtho-1,2-dithiole-3 -thiones with acetylenic reagents, but the photo-reaction with alkenes produces adducts which are in equilibrium with dimers (4,5). It is also reported that o-xylylenes may undergo dimerisation (6) but a more closely related imino-o-quinomethide only shows a [2 + 41 type addition (7).…”
Section: Introductionmentioning
confidence: 99%